1996
DOI: 10.2307/1243844
|View full text |Cite
|
Sign up to set email alerts
|

The Former Soviet Union and the World Wheat Economy

Abstract: The impacts of the former Soviet Union leaving the world wheat market as a consistent net importer are investigated using a modified spatial trade equilibrium model. The simulation results suggest that the former Soviet Union, following Bigman's stochastic trade hypothesis, can have a stabilizing role in the future world wheat economy. Copyright 1996, Oxford University Press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Cramer et al () employed the SEM to analyze the impacts of trade liberalization in the world rice market. Jones et al () constructed a SEM to study the impacts of Russia becoming a consistent importer in the world wheat market. Fuller et al () employed a spatial multi‐product equilibrium model featuring the USA–Mexico long‐grain rice trade to determine the effect of Mexico's removal of tariffs on US rough and milled rice exports.…”
Section: Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cramer et al () employed the SEM to analyze the impacts of trade liberalization in the world rice market. Jones et al () constructed a SEM to study the impacts of Russia becoming a consistent importer in the world wheat market. Fuller et al () employed a spatial multi‐product equilibrium model featuring the USA–Mexico long‐grain rice trade to determine the effect of Mexico's removal of tariffs on US rough and milled rice exports.…”
Section: Empirical Modelmentioning
confidence: 99%
“…For a SEM with a specific tariff , the net‐welfare function (sum of producer surplus, consumer surplus and net of transport costs) is strictly concave and maximization of this function subject to the constraints (a) no excess demand and (b) no excess supply will yield a global maximum and economic equilibrium. Most SEM studies (Jones et al, ) use a specific tariff in their analysis. Since the Uruguay Round, all tariffs are implemented in the form of ad valorem tariffs and thus it is important to incorporate ad valorem tariffs in the SEM for trade policy analysis.…”
Section: Empirical Modelmentioning
confidence: 99%
“…For example, Boyd and Krutilla (1987) utilised the SEM to examine the US tariff on lumber imports from Canada and found that the US tariff harms Canadian lumber producers, but voluntary export restraint by Canada benefits Canadian lumber producers. Jones et al (1996) employed the SEM to study the effects of the former Soviet Union on the world wheat market and concluded that the stability of the wheat market is impacted by unpredictable wheat production in the former Soviet Union. Devadoss et al (2009) developed a SEM for the world apple market to study the impacts of free trade.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM model has been extensively used for trade policy analyses: the impacts of Mexican tariff on US apple exports, the influence of former Soviet Union on world wheat market(Jones et al, 1996), a free trade analysis in the wheat market(Gómez-Plana & Devadoss, 2004), the consequences of United States-Canadian lumber dispute(Devadoss, 2006), and the effects of United States-Brazil cotton dispute on the world market. The advantage of SEM is that it analyzes in great detail the effects of policy changes on trade flow reallocations, prices, supply, demand and welfare of each country in the partial equilibrium or cross commodity framework.…”
mentioning
confidence: 99%